LEGAL REVIEW OF NARCOTICS ABUSE AND PREVENTION EFFORTS - Deni Karnius Zebua; Mhd. Azhali Siregar; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
Drug abuse is a serious problem that impacts not only health but also social, economic, legal, and national security consequences. While narcotics have legitimate uses in medicine and research, they are often misused beyond these purposes, leading to dependency, impaired quality of life, and even threatening the future of the younger generation. This study examines two important aspects: efforts to prevent drug abuse and law enforcement against drug crimes in Indonesia. The method used is normative legal research with a conceptual approach, referring to laws and regulations, legal doctrine, and relevant literature. The results show that preventing drug abuse requires an integrated strategy through promotive, preventive, curative, rehabilitative, and repressive approaches. Promotive and preventive approaches serve to provide education and build public awareness from an early age, while curative and rehabilitative approaches play a role in helping addicts break free from dependence. On the other hand, a repressive approach is implemented to take firm action against producers, distributors, and users who violate the law. Furthermore, law enforcement against drug abuse is based on Law Number 35 of 2009, which stipulates severe criminal sanctions, including the death penalty, and requires rehabilitation for addicts. Law enforcement is carried out through penal and non-penal channels, involving law enforcement officials, rehabilitation institutions, and the wider community. Major challenges include internationally organized drug crime networks, weak oversight, and the potential for corruption among officials. Therefore, drug eradication cannot be left to one sector alone but must involve synergy between the government, law enforcement, families, schools, and the community. Comprehensive efforts that combine legal and health aspects are expected to reduce drug abuse rates and protect the nation's future generations from the threat of destruction.